NEW SPECIES OF AULACOPHORA FROM SABAH, MALAYSIA (COLEOPTERA: CHRYSOMEUDAE: GALERUCINAE) - MOHAMED S. MOHAMEDSAID (Research Center for Biology, 1994)
Three new species of Aulacophora are described from Sabah,Malaysia: A. danumensis n.sp., A. irpa n.sp. and A. kinabaluensis n.sp.Aulacophora coffeae 'and A. indica are reported as new records forBorneo.